Can Blockchain-adoption Announcements Create Market and Operating value in Banks? Evidence from an Event Study for Global Banks initiatives - Said, Nourhan (AUC Knowledge Fountain, 2026)
This thesis offers quantitative work in exploring the market value and operation advantages associated with blockchain initiatives in listed banks. We utilized an event study approach to analyze the market value added to banks adopting blockchain technology on a short term. The sample consist of 126 event observations spanning 30 different countries in the period between 2016 and 2024. The study also focuses on the signals and cues that drive the changes in the banks’ abnormal returns and cumulative abnormal returns. Different project attributes like the blockchain type, blockchain application, and objective as well as bank characteristics like the bank size were analyzed using OLS regression model. The results showed that banks announcing blockchain initiatives experience a positive abnormal return on the event date and a positive cumulative abnormal return over the event window of [-2,2]. In addition, this paper uniquely studies the long-term impact of blockchain initiatives on banks’ operating performance by utilizing a one-to-portfolio matching method. This study examines three operational metrics: the operating income, revenue from business operations and return on asset by comparing the sample banks with a control group of banks over a 4-year period. The results showed an improvement in all three metrics indicating a positive impact and a performance advantage of banks adopting blockchain compared to other banks. The study provides recommendations on how to maximize the banks’ benefit from future blockchain projects.